Investigation of the Secretory Pathway in Trichomonas vaginalis Argues against a Moonlighting Function of Hydrogenosomal Enzymes - Rada, Petr; Kellerová, Pavlína; Verner, Zdeněk; Tachezy, Jan (Journal of eukaryotic microbiology, 2019)
The enzymes pyruvate ferredoxin oxidoreductase (PFO), malic enzyme (ME), and the α- and β-subunits of succinyl-CoA synthetase (SCS) catalyze key steps of energy metabolism in Trichomonas vaginalis hydrogenosomes. These proteins have also been characterized as the adhesins AP120 (PFO), AP65 (ME), AP33, and AP51 (α- and β-SCS), which are localized on the cell surface and mediate the T. vaginalis cytoadherence. However, the mechanisms that facilitate the targeting of these proteins to the cell surface via the secretory pathway and/or to hydrogenosomes are not known. Here we adapted an in vivo biotinylation system to perform highly sensitive tracing of protein trafficking in T. vaginalis. We showed that α- and β-SCS are biotinylated in the cytosol and imported exclusively into the hydrogenosomes. Neither α- nor β-SCS is biotinylated in the endoplasmic reticulum and delivered to the cell surface via the secretory pathway. In contrast, two surface proteins, tetratricopeptide domain-containing membrane-associated protein and tetraspanin family surface protein, as well as soluble-secreted β-amylase-1 are biotinylated in the endoplasmic reticulum and delivered through the secretory pathway to their final destinations. Taken together, these results demonstrate that the α- and β-SCS subunits are targeted only to the hydrogenosomes, which argues against their putative moonlighting function.
Keywords: Trichomonas vaginalis; sukcinát-CoA-ligasy; Secretory Pathway; Protein Transport; biotinylace; Protozoan Proteins; Biotinylation; protozoální proteiny; transport proteinů; sekreční dráha; Succinate-CoA Ligases